The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.1186/s11689-020-9307-8
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive correlates of attention-deficit hyperactivity disorder in children and adolescents with high intellectual ability

Abstract: Background: There is an ongoing debate as to whether attention-deficit hyperactivity disorder (ADHD) in highly intelligent individuals has a similar presentation as in average intelligent individuals. The aim of this study was to examine the cognitive correlates of ADHD in highly intelligent children and adolescents with ADHD. Method: Two independent samples (N = 204 and N = 84) of (1) high intelligence quotient (IQ) (IQ ≥ 120) children and adolescents with ADHD were used, carefully matched on age, gender, ADH… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 36 publications
0
9
0
Order By: Relevance
“…Healey et al investigated the correlation between ADHD and creativity and found that there were no differences in the creative ability of the ADHD and the control group. Furthermore, this study showed that, despite the significant levels of ADHD symptomatology displayed by gifted children, the full criteria for ADHD were not met 18 ; similarly, the connection between ADHD and intellectual giftedness or creativity was not established in another study by Healey et al 28 Likewise, Cadenas et al 19 indicated that the highly intelligent group with ADHD performed at the same level as the average intelligent control group on the Wechsler Intelligence Scale for Children or Wechsler Adult Intelligence Scale-III. Diagnostic methods seemed to modify the associations between ADHD and giftedness.…”
Section: Giftedness and Attention-deficit/hyperactivity Disordermentioning
confidence: 66%
“…Healey et al investigated the correlation between ADHD and creativity and found that there were no differences in the creative ability of the ADHD and the control group. Furthermore, this study showed that, despite the significant levels of ADHD symptomatology displayed by gifted children, the full criteria for ADHD were not met 18 ; similarly, the connection between ADHD and intellectual giftedness or creativity was not established in another study by Healey et al 28 Likewise, Cadenas et al 19 indicated that the highly intelligent group with ADHD performed at the same level as the average intelligent control group on the Wechsler Intelligence Scale for Children or Wechsler Adult Intelligence Scale-III. Diagnostic methods seemed to modify the associations between ADHD and giftedness.…”
Section: Giftedness and Attention-deficit/hyperactivity Disordermentioning
confidence: 66%
“…Previous studies conducted with children and adolescents have reported a negative association between ADHD symptoms and WM regardless of IQ-score (Cadenas et al, 2020; Rohrer-Baumgartner et al, 2014). Similar findings were observed in studies in adults, although those studies mostly provided indirect support since none explicitly tested the interaction between WM and IQ (Antshel et al, 2010; Brown et al, 2009).…”
Section: Discussionmentioning
confidence: 88%
“…Attention problems were the most common predictors of functional impairments at school: school progress, additional phone calls to parents due to children's school problems, and performance below ability, including in individuals with high IQ. Also in the Netherlands, the study by Cadenas et al (2020) examined the cognitive correlates of ADHD in highly intelligent children and adolescents with ADHD. Two independent samples (n=204 and n=84) were combined into four groups: (a) children and adolescents with high intelligence quotient (IQ ≥120) and ADHD, (b) control participants with high intelligence, (c) ADHD participants with average intelligence (IQ between 90 and 110), and (d) control participants with average intelligence.…”
Section: Resultsmentioning
confidence: 99%
“…The studies also revealed that the characteristics and symptoms of ADHD manifest similarly in individuals with high and medium intelligence (Cadenas et al, 2020;Katusic et al, 2011;Minahim & Rohde, 2015), which may hinder the identification of giftedness by the family and the school as, in this case, students with high intelligence tend to be recognized only by their manifestation of the attributes of the disorder. In this situation, ADHD generally masks giftedness by increasing the externalization of socio-emotional difficulties and reducing academic performance to medium levels (Mullet & Rinn, 2015).…”
Section: Discussionmentioning
confidence: 99%